Climate advisory services in Myanmar generate high returns through private digital platforms - Swaans, Cornelis; Dela Rueda, Justin; Khaung, Ye; McGrath, Quyen (2025)
Using Village Link’s digital climate advisory services (DCAS), 243 farmers, representing 26,064 rice farmers in Myanmar’s Ayeyarwady Delta, have avoided production losses and increased their yields and income by adopting timely climate information. In 2024, The average yields of the treatment group (3.77 mt/ha) and control group (3.13 mt/ha) shows a 20.4% yield increase. The difference in yield and quality led to a gross income increase of 31.9% (US$ 1225/ha versus US$ 928) and a net income increase of 316% (US$ 237/ha versus US$ 57/ha) after reduction of input costs, resulting in a high investment potential DCAS with a total net present value (NPV) of USD 51.73 million and a benefit-cost ratio (BCR) of 155:1.